PEMANFAATAN DISTRIBUSI HARTA DALAM KONSEPSI KEADILAN EKONOMI ISLAM MELALUI ZAKAT - Dadang Heru Jatmiko (Al-Hijrah: Journal of Islamic Economics And Banking, 2024)
The concept of economic justice in Islam covers various important aspects such as wealth distribution, fairness in business, and fair management of profits. Unlike capitalist and socialist economic systems, Islamic economics emphasizes the equal distribution of wealth and equal rights for every individual to manage factors of production. In Islam, economic justice aims to achieve common good, avoid economic inequality, and prohibit all forms of exploitation, monopoly, and hoarding of wealth. This system emphasizes the importance of distributive justice, where each individual gets their rights according to the contribution they make without exploiting others. Efforts for socio-economic justice are implemented through policies such as zakat, alms, and fair distribution of wealth, as regulated in Islamic law. In addition, the concept of wealth and consumption in Islamic economics is also regulated by principles that maintain a balance between physical and spiritual needs, as well as between individual and community rights. Islamic economics ensures that every individual has access to the resources and wealth needed for the common good.